Peningkatan Proeses Pembelajaran Tematik Terpadu Menggunakan Model Problem Based Learning Di Kelas IV - Ramadani, Uci Tri; Mansurdin, Mansurdin (Universitas Negeri Padang, 2022)
This study is motivated by the problem found in the field where a teacher used a prescribed lesson plan without adapting it following the situation and the condition of the students. As a result, the integrated thematic learning process is not student oriented and does not respond to the actual problem. One of the solutions to overcome such problem is using Problem Based Learning (PBL) model. This study aims at describing the improvement of students’ integrated thematic learning using Problem Based Learning (PBL) model. This study used both qualitative and quantitative approaches, and used classroom action research as the design. This study was conducted at SDN 34 Aia Pacah. The result show that: 1) the assessment result of the lesson plan in Cycle 1 is 81.25%, categorized in the “good” qualification (G), it increases to 96.87% in Cycle II, categorized in the “very good” qualification (VG); 2) the learning implementation result viewed from the teacher aspect in Cycle 1 is 87.50%, categorized in the “good” qualification (G), it increases to 96.42% in Cycle II, categorized in the “very good” qualification (VG); 3) the learning implementation result viewed from the student aspect in Cycle 1 is 87.50%, categorized in the “good” qualification (G), it increases to 96.42% in Cycle II, categorized in the “very good” qualification (VG). Thus, it can be concluded that using problem based learning (PBL) model can improve the learning process of the elementary school students at SDN 34 Aia Pacah.